Patterns of herbivory and leaf morphology in two Mexican hybrid oak complexes: Importance of fluctuating asymmetry as indicator of environmental stress in hybrid plants - Cuevas-Reyes, Pablo; Canché-Delgado, Armando; Maldonado-López, Yurixhi; Fernandes, G. Wilson; Oyama, Ken; González-Rodríguez, Antonio (Ecological indicators, 2018)
•Hybrid zones of Mexican oaks act as potential sinks for herbivores colonization.•Different patterns of leaf morphology were found in the two hybrid oak complexes.•Hybrid individuals show higher levels of fluctuating asymmetry and herbivory.•These findings suggest higher levels of genetic or environmental stress in hybrids. Interspecific hybridization is a prevalent process in plant species that may have different ecological and evolutionary consequences. Interactions with herbivorous insects may be altered because of hybridization among host plants. These changes result from the morphological, physiological and chemical traits expressed in hybrid individuals. Therefore, it is of interest to document the changes in traits such as leaf morphology and their consequences on patterns of herbivory by insects in hybrid complexes of plants. Another useful indicator that may serve to evaluate developmental instability resulting from genetic or environmental stress in hybrid plants is fluctuating asymmetry. In this study, we used two previously genetically characterized complexes of hybridizing Mexican oaks as models to compare and understand the relationships between leaf morphology, fluctuating asymmetry and herbivory levels in parental and hybrid individuals. Results indicated that in the Quercus affinis × Q. laurina complex, hybrid individuals show a distinct morphology in relation to the parental species, while in the Q. magnoliifolia × Q. resinosa complex, hybrids were similar to Q. resinosa. In both hybrid complexes, our results show that hybrid individuals have higher levels of fluctuating asymmetry and herbivory levels, which may reflect higher levels of genetic or environmental stress in comparison to the parental species. These results might help explain why oak species usually remain distinct despite the high frequency of hybridization characteristic of the genus.